1993
DOI: 10.1021/j100139a022
|View full text |Cite
|
Sign up to set email alerts
|

Chain-length dependence of the third-order polarizability of disubstituted polyenes: effects of end groups and conjugation length

Abstract: Various a,o-disubstituted polyenes of increasing length and bearing various donor and acceptor end groups have been synthesized in order to investigate the chain-length dependence of their second-order hyperpolarizability y. Both symmetric polyenes bearing electron-withdrawing or electron-donating end groups and asymmetric donor-acceptor (push-pull) polyenes have been studied for the same donor/acceptor couple. Values of y have been obtained through the electric field induced second-harmonic generation (EFISH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
1
4

Year Published

1995
1995
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 3 publications
2
59
1
4
Order By: Relevance
“…[5][6][7][8] In a recent theoretical investigation, we have analyzed in depth the influence on the cubic nonlinearities of grafting in both symmetric and asymmetric ways of electron-donating and electronwithdrawing moieties to a polyene segment. 9 According to the results of these calculations, 8,9 the major contribution to the static value of the third-order polarizabilities, ␥, of donor-acceptor polyene derivatives in weakly polar media originates from the so-called dipolar term that involves the difference between the dipole moments in the ground state and in the lowest charge-transfer excited state; in that case, a two-state model should be adequate to describe both the quadratic and cubic dynamic response of push-pull compounds near resonance, a feature which has been demonstrated by Dirk and Kuzyk in the case of p-nitroaniline.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] In a recent theoretical investigation, we have analyzed in depth the influence on the cubic nonlinearities of grafting in both symmetric and asymmetric ways of electron-donating and electronwithdrawing moieties to a polyene segment. 9 According to the results of these calculations, 8,9 the major contribution to the static value of the third-order polarizabilities, ␥, of donor-acceptor polyene derivatives in weakly polar media originates from the so-called dipolar term that involves the difference between the dipole moments in the ground state and in the lowest charge-transfer excited state; in that case, a two-state model should be adequate to describe both the quadratic and cubic dynamic response of push-pull compounds near resonance, a feature which has been demonstrated by Dirk and Kuzyk in the case of p-nitroaniline.…”
Section: Introductionmentioning
confidence: 99%
“…The configuration and conformation of carotenoids, which is a typical -conjugated molecule, are well characterized compared to -conjugated polymers; therefore, the mechanism that produces the large optical nonlinearities in carotenoids have been extensively studied. [1][2][3][4][5][6][7][8][9][10] For example, it has been shown that introduction of polar functional groups into carotenoids is a promising way to enhance their optical nonlinearity. 9,10 This increase in the magnitude of the optical nonlinearity, however, has the unfortunate side effect of losing optical transparency in the visible wavelength region.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] For example, it has been shown that introduction of polar functional groups into carotenoids is a promising way to enhance their optical nonlinearity. 9,10 This increase in the magnitude of the optical nonlinearity, however, has the unfortunate side effect of losing optical transparency in the visible wavelength region. The work described here is motivated by finding other strategies that simultaneously improve the magnitude of the optical nonlinearity and such serious side effects of losing transparency.…”
mentioning
confidence: 99%
“…Analoge Befunde wurden auch für die OEs mit carotinoiden Brücken erhalten (siehe Abschnitt 3.1). [54,113,115,116,117,119] Fünfringheterocyclen, z. B. Für die Hyperpolarisierbarkeiten b und g wurden auf der Basis der Messdaten immer wieder empirische Gesetzmäßig-keiten aufgestellt, die den Einfluss von Substituenten [71] und bei Oligomeren den Einfluss von n [54,56,57,110,112,116,129] wiedergeben sollten, z.…”
Section: Oligomere Mit D-p-a-p-d-oder A-p-d-p-a-strukturunclassified
“…So gibt es Beispiele, bei denen der g-Wert von D-p-AVerbindungen zwischen den g-Werten von D-p-D-und A-p-A-Verbindungen liegt. [116] Die von Flytzanis und anderen vorgeschlagenen Potenzgesetze (27) und (28) [124,125] …”
Section: Oligomere Mit D-p-a-p-d-oder A-p-d-p-a-strukturunclassified